Fostering Self-Management of Everyday Memory in Older Adults: A New Intervention Approach - Hertzog, Christopher; Pearman, Ann; Lustig, Emily; Hughes, MacKenzie (Frontiers in Psychology, 2021)
Traditional memory strategy training interventions improve older adults’ performance on tests of episodic memory, but have limited transfer to episodic memory tasks, let alone to everyday memory. Likewise, intensive practice in complex cognitive task environments may benefit tasks where cognitive processes (e.g., attentional control) honed with practice are also beneficial for performance. Here too there is little evidence that such training helps older adults address cognitive demands in everyday life. We argue that an alternative approach is needed to assist older adults to compensate for age-related cognitive declines and to maintain functional capacity in their own natural ecologies. We outline a set of principles regarding how interventions can successfully train older adults to increase successful goal pursuit to reduce risks of everyday memory failures. A major theme is that individuals can use simple but effective strategies to good effect when the focus is on how to use these skills in everyday contexts. Another major theme is that everyday memory errors often arise when habits and routines are thwarted or interrupted. We argue that training individuals to use metacognitive self-regulatory strategies to proactively manage formulation and pursuit of daily goals can compensate for age-related cognitive changes and increase the likelihood of goal attainment. We then describe an intervention approach that instantiates these principles in a multi-modal intervention that is unique in its three-phase approach: (1) individualized assessment of an individual’s current approaches to self-regulation; (2) training memory strategies, self-management skills, and new habits of mind in a group training context; and (3) a behavioral shaping period in which individuals receive coaching and feedback on their efforts to use trained procedures to improve everyday cognition. A recently completed study conducted an initial test of the intervention, with highly encouraging results. We advocate further efforts to replicate, extend, and fine-tune this type of intervention. The ultimate goal is to be able to deliver the intervention in a way that increases its potential reach, including to subpopulations of older adults at risk for everyday cognitive impairments.